1981
DOI: 10.1002/prep.19810060606
|View full text |Cite
|
Sign up to set email alerts
|

Mach Reflection in Condensed Explosives

Abstract: Machsche Reflexion in kondensierten SprengstoffenIn einem Versuchsgerat wurden zwei transparente, kondensierte Sprengstoffe mit unterschiedlichen Detonationsgeschwindigkeiten koaxial so angeordnet, dal3 die Machsche Reflexion in dem langsameren Sprengstoff auftritt (overdriven detonation). Aufgrund der Transparenz der Sprengstoffe gibt dieser Aufbau in Verbindung mit einer Streak-Kamera die Moglichkeit , den Vorgang der Machschen Reflexion kontinuierlich aufzuzeichnen sowohl vor als auch nach seinem Auftreten.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…(11)(12)(13)(14) and Eqs. (18)(19)(20), values of P 2 , u 2 , 1 2 (v 2 ), q 2 , y II , u 3t , and 1 3t can be determined.…”
Section: Mathematical Description Of Detonation Waves In Dlc Chargesmentioning
confidence: 99%
See 1 more Smart Citation
“…(11)(12)(13)(14) and Eqs. (18)(19)(20), values of P 2 , u 2 , 1 2 (v 2 ), q 2 , y II , u 3t , and 1 3t can be determined.…”
Section: Mathematical Description Of Detonation Waves In Dlc Chargesmentioning
confidence: 99%
“…There are many experimental results and numerical prediction of reflection of detonation wave in the related literature [12,13,18,19]. To date there is no accurate method of predicting the height of Mach stem in irregular reflection of detonation wave.…”
Section: Mach Stem Height Predictionmentioning
confidence: 99%
“…Müller [14] developed a plane detonation wave device to investigate the Mach reflection disturbed by rarefaction waves from the boundaries. Krishnan et al [15] presented a Mach disc configuration to measure the dimension and velocity of Mach reflection, and the device provided accurate and continuous data generation for effectively understanding the Mach stem. Attetkov et al [16] studied the Mach reflection of cylindrical detonation waves and found that the propagation of a three-wave configuration in low-density explosives was related to several specific parameters of the initial state of the explosive.…”
Section: Introductionmentioning
confidence: 99%
“…Krishnan et al. [15] presented a Mach disc configuration to measure the dimension and velocity of Mach reflection, and the device provided accurate and continuous data generation for effectively understanding the Mach stem. Attetkov et al.…”
Section: Introductionmentioning
confidence: 99%
“…Dunne [5,6] conducted theoretical and experimental studies on the Mach reflection of a detonation wave in condensed high-explosives to determine the critical angle for the Mach reflection and the pressure in the centre of the Mach stem. Krishnan et al [7] presented experimental results of Mach reflection in condensed high explosives viz., triple point growth angle, Mach-disc configuration and pressure. Trotsyuk et al [8] investigated the effect of the existence of strong transverse waves on the Mach stem front and the steadiness of Mach reflection.…”
Section: Introductionmentioning
confidence: 99%